Peningkatan Hasil Belajar PKn Melalui Pendekatan Problem Solving pada Siswa Kelas V SD Inpres Andi Tonro Kota Makassar - Andi Baso; Nasrun Hasan (JED (Jurnal Etika Demokrasi), 2018)
The main problem of this study is the low learning outcomes of students, so the purpose of this study is to improve the learning outcomes of Civics through problem solving approaches in grade V students Inpres Andi Tonro Makassar. Research This research belongs to classroom action research. The subjects of this study were all students of grade V SD Inpres Andi Tonro Kota Makassar which amounted to 41 students consisting of 26 Men and 15 Women. The results showed the use of problem solving application can improve the learning outcomes of Civics in grade V SD Inpres Andi Tonro Makassar. It can also be seen from the average value in cycle I that is 70.37 and is in the medium category and increased in cycle II to 81.34 and is in the high category.Keywords: Learning outcomes, problem solving, students.